Systematic Literature Review: Adaptation and Psychological Changes of Pregnant Women with Diagnosis Gestational Diabetes Mellitus - Arista Apriani (Gaster, 2021)
Gestational diabetes mellitus (GDM) accounts for 3-25% of all pregnancies in the world. The diagnosis of GDM in pregnant women has physical as well as psychological effects that can be considered for planning a healthy lifestyle promotion strategy that is the first line of treatment. The aim was to examine the literature on the adaptation and psychological changes of pregnant women with the diagnosis of GDM. The method uses a focus step review, the PEOS framework, identifies relevant studies from Pubmed and Proquest 2015-2019, filtering data with PRISMA Flowchart, assessing the quality of studies using CAPS. Results: From 929 articles, 13 articles indexed by Scopus Q1 and Q2 were analyzed. Thematic analysis obtained results from adjusting the diagnosis of GDM through stages of distress and fear, realizing the necessary changes, learning to manage GDM, finding motivation and compliance, feeling various psychological impacts, some consider it a call to make lifestyle changes during pregnancy. Conclusion: adaptation of pregnant women to the diagnosis of GDM, changes in attitude and anxiety from time to time, ultimately leading to acceptance of the condition and the best management. The psychological changes of the mother with a diagnosis of GDM find it difficult to come to terms with her condition, partly as a call to make lifestyle changes during pregnancy.